Therapeutic Potential of Withania coagulans Dunal. (Rishyagandha) on Diabetes Mellitus Type- II: A Review - Sony (International Research Journal of Ayurveda & Yoga, 2024)
In Ayurveda there are many classical herbs frequently used in the treatment of diabetes mellitus type-II. In recent years, some new herbs have showed potential for the management of DM-II. One of such herbs is Withania coagulans Dunal. (Doda Paneer) which has profound hypoglycemic activity. W. coagulans has been acclaimed Rishyagandha in Ayurveda and used for nervine tonic, debility, insomnia, aphrodisiac, and rejuvenator. Rishyagandha (W. coagulans) is described in Charaka Samhita in “Brihaniya Mahakashaya”and “Madhur Skandha Dravya”. Acharya Charaka has described two types of therapies for Prameha, Brihana for krish and dourbala pramehi and Samshodhana for sthula and balvan pramehi. So in krisha and dourbala patient, Rishyagandha improves the In Ayurveda there are many classical herbs frequently used in the treatment of diabetes mellitus type-II. In recent years, some new herbs have showed potential for the management of DM-II. One of such herbs is Withania coagulans Dunal. (Doda Paneer) which has profound hypoglycemic activity. W. coagulans has been acclaimed Rishyagandha in Ayurveda and used for nervine tonic, debility, insomnia, aphrodisiac, and rejuvenator. Rishyagandha (W. coagulans) is described in Charaka Samhita in “Brihaniya Mahakashaya”and “Madhur Skandha Dravya”. Acharya Charaka has described two types of therapies for Prameha, Brihana for krish and dourbala pramehi and Samshodhana for sthula and balvan pramehi. So in krisha and dourbala patient, Rishyagandha improves the quality of Dhatu production, promotes the Ojas formation by its Brimhana properties. The active compound withanolide isolated from the plant are considered to have hypoglycemic activity. Aqueous extract of the fruit significantly lower the blood glucose level. A 30 days study of Aqueous extracts on streptozotocin induced Swiss albino mice showed reduction of 48.5 and 52.6% in fasting blood glucose and postprandial glucose levels, respectively and prove to be better alternative for Hypoglycemic agents.